The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1159/000503021
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis of the Musculoskeletal System

Abstract: Objective: Recent studies indicate that India is an endemic region for Burkholderia pseudomallei infection. We aimed to describe the clinical presentation of B. pseudomallei infection of the musculoskeletal system and summarise the various treatment modalities used in our clinical practice. Subjects and Methods: Patients with confirmed microbiological diagnosis of B. pseudomallei infection involving the musculoskeletal system treated from January 2007 to December 2016 with a minimum follow-up of 1 year were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…As regards musculoskeletal involvement, of 26 patients from South India with musculoskeletal melioidosis, 15 (58%) had osteomyelitis, 10 (38%) had septic arthritis, and one (4%) had soft tissue abscess. 38 From outside India, localized melioidosis as the predominant manifestation was seen in a study from Thailand in which, of 134 patients from January 2002 to June 2011, the majority cases (62.7%) were localized unifocal or multifocal infection without bacteremia. 10 A study from Bangladesh over a prolonged period from 1961 to 2017 noted musculoskeletal (21, 43%), organ abscess/deep-seated abscess (13, 27%), and cutaneous (13, 27%) lesions to be the predominant manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards musculoskeletal involvement, of 26 patients from South India with musculoskeletal melioidosis, 15 (58%) had osteomyelitis, 10 (38%) had septic arthritis, and one (4%) had soft tissue abscess. 38 From outside India, localized melioidosis as the predominant manifestation was seen in a study from Thailand in which, of 134 patients from January 2002 to June 2011, the majority cases (62.7%) were localized unifocal or multifocal infection without bacteremia. 10 A study from Bangladesh over a prolonged period from 1961 to 2017 noted musculoskeletal (21, 43%), organ abscess/deep-seated abscess (13, 27%), and cutaneous (13, 27%) lesions to be the predominant manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,27 Overall, an excellent outcome was observed similar to other studies of localized cutaneous or musculoskeletal infections, where a high rate of resolution has been seen. 38,42 Susceptibility studies from India and elsewhere reveal that antimicrobial resistance in B. pseudomallei has been extremely low to most of the antibiotics, except amoxicillinclavulanic acid and trimethoprim-sulfamethoxazole. 32,43 A study of more than 4,000 B. pseudomallei isolates in Thailand and more than 600 isolates in Singapore reported ceftazidime resistance at 0.5%, whereas multiple smaller studies demonstrated 100% susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 7.6%–14.4% of melioidosis cases have musculoskeletal involvement ( 13 – 15 ). A longer duration of infection appears to increase the risk for bone and joint involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Melioidosis, an infection caused by the Gramnegative bacterium Burkholderia pseudomallei is associated with a broad spectrum of clinical manifestations involving different organ systems [1]. Musculoskeletal melioidosis is an uncommon but well-recognized manifestation of the disease [2,3]. Here, we report a case of pyomyositis with abscesses in the obturator externus and adductor muscles.…”
Section: Introductionmentioning
confidence: 92%